Sounding Islam: Voice, Media, and Sonic Atmospheres in an Indian Ocean World - Eisenlohr, Patrick (University of California Press, 2018)
"Sounding Islam investigates the sonic dimensions of religion, combining perspectives from the anthropology of media, the anthropology of semiotic mediation, and sound studies. Based on long-term ethnographic research on devotional Islam in Mauritius, Patrick Eisenlohr explores how the voice, as a site of divine manifestation, becomes refracted in media practices that have become integral parts of religion. At the core of Eisenlohr's concern is the interplay of voice, media, affect, and listeners' experience, especially within the context of Mauritian Islamic practices. The work is a contribution to the anthropological study of sound, media, and religious experience and a rich study of Mauritius, diasporic South Asian communities, and global Islam."--Provided by publisher.